Decreased hippocampal brain‐derived neurotrophic factor and impaired cognitive function by hypoglossal nerve transection in rats - Kim, Doyun (J Cell Mol Med, 2017)
The hypoglossal nerve controls tongue movements, and damages of it result in difficulty in mastication and food intake. Mastication has been reported to maintain hippocampus‐dependent cognitive function. This study was conducted to examine the effect of tongue motor loss on the hippocampus‐dependent cognitive function and its underlying mechanism. Male Sprague Dawley rats were subjected to the initial training of Morris water maze task before or after the bilateral transection of hypoglossal nerves (Hx). When the initial training was given before the surgery, the target quadrant dwelling time during the probe test performed at a week after the surgery was significantly reduced in Hx rats relative to sham‐operated controls. When the initial training was given after the surgery, Hx affected the initial and reversal trainings and probe tests. Brain‐derived neurotrophic factor (BDNF) expression, cell numbers and long‐term potentiation (LTP) were examined in the hippocampus on the 10(th) day, and BrdU and doublecortin staining on the 14(th) day, after the surgery. Hx decreased the hippocampal BDNF and cells in the CA1/CA3 regions and impaired LTP. BrdU and doublecortin staining was decreased in the dentate gyrus of Hx rats. Results suggest that tongue motor loss impairs hippocampus‐dependent cognitive function, and decreased BDNF expression in the hippocampus may be implicated in its underlying molecular mechanism in relation with decreased neurogenesis/proliferation and impaired LTP.